Searching for Antimicrobial-Producing Bacteria from Soils through an Educational Project and Their Evaluation as Potential Biocontrol Agents - Mario Sergio Pino-Hurtado; Rosa Fernández-Fernández; Carmen Torres; Beatriz Robredo (MDPI AG, 2023)
Antimicrobial resistance (AMR) is a serious threat to public health due to the lack of effective drugs to combat infectious diseases, which generates the need to search for new antimicrobial substances. In this study, the potential of soil as a source of antimicrobial-producing bacteria (APB) was investigated and the importance of the connection between education and science was emphasized, using service-learning methodologies. Sixty-one soil samples were collected, and 1220 bacterial isolates were recovered. Eighteen of these isolates showed antimicrobial activity against at least 1 of the 12 indicator bacteria tested (including multidrug-resistant and relevant pathogens). The 18 APB were identified by MALDI-TOF and 6 different genera (Bacillus, Brevibacillus, Lysinobacillus, Peribacillus, Streptomyces, and Advenella) and 10 species were identified. The 18 APB were tested for antifungal activity against four phytopathogenic fungi (Botritis cynerea, Lecanicillium fungicola, Trichoderma harzianum, and Cladobotryum mycophilum). Moreover, the antibiotic susceptibility of APB was tested using the disk-diffusion method as well as their β-hemolytic activity (important safety criteria for potential future applications). A total of 10 of the 18 APB were able to inhibit at least 50% of indicator bacteria tested, including methicillin-resistant Staphylococcus aureus (MRSA), among others. A total of 4 of the 18 APB (3 Bacillus pumilus and 1 Bacillus altitudinis) showed inhibitory activity against two of the four fungal pathogens tested (B. cinerea and L. fungicola), as well as against 5-7 of the 12 bacterial pathogen indicators; these 4 isolates showed susceptibility to the antibiotics tested and lacked β-hemolytic activity and were considered promising APB for use as potential biocontrol agents. In addition, one Brevibacillus laterosporus strain had activity against 83% of indicator bacteria tested including Escherichia coli, MRSA and other methicillin-resistant staphylococci, as well as vancomycin-resistant enterococci (but not against fungi). These results show that soil is a source of APB with relevant antibacterial and antifungal activities, and also emphasize the importance of education and science to raise public awareness of the AMR problem and the strategies to control it.